Limit behavior of the distribution of the ruin moment of a modified risk process - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For modified risk process with instantaneous reflection at the point B > 0 under which the considered process ζ(t) = ζ_B, μ(t), ζ(0) = u, 0 ≤ u ≤ B, returns in the initial state u, we investigate the limit behavior of generating function of the first ruin moment as u → B and B → ∞.